Cu/Fe oxide integrated on graphite felt for degradation of sulfamethoxazole in the heterogeneous electro-Fenton process under near-neutral conditions. (June 2022) - Fu, Ao; Liu, Zhibin; Sun, Zhirong
Abstract: In the heterogeneous electro-Fenton (EF) system, high-efficiency and durable materials have attracted widespread attention as cathodes for degradation of refractory organic pollutants. In this study, a stable Cu/Fe oxide modified graphite felt electrode (Cu0.33 Fe0.67 NBDC-300/GF) was fabricated via a one-step hydrothermal method and subsequent thermal treatment, which used a bimetallic metal–organic framework (MOF) with 2-aminoterephthalic acid (NH2 BDC) ligand as the precursor. The Cu0.33 Fe0.67 NBDC-300/GF electrode was used as the cathode for sulfamethoxazole (SMX) degradation in the heterogeneous EF process. The coexistence of the Fe II /Fe III and Cu I /Cu II redox couples significantly accelerates the regeneration of Fe II and promotes the generation of active free radicals (OH and O2 − ). Fe IV was detected during the process, which indicates that the high-valent iron-oxo species was produced in near-neutral pH conditions. The removal efficiency of SMX (10 mg L −1 ) can reach 100.0% within 75 min over a wide pH range (4.0–9.0). After five cycles, the electrode retained a high stability and an outstanding catalytic capacity. Furthermore, the mechanisms and pathways for SMX degradation were proposed, the products and intermediates of SMX were analyzed, and the toxicity was evaluated. It was found that the toxicity decreased after degradation. This study displays a novel strategy for building an efficient and stable self-supporting electrode for treating antibiotic wastewater. Graphical abstract: Image 1 Highlights: A modified graphite felt using a bimetallic MOF as the precursor is prepared. Excellent SMX removal is achieved over a wide pH range. The synergistic effect between Fe and Cu facilitates the catalytic process. Surface-bound .OH is the major contributor, and high-valent iron-oxo is produced. The toxicities of SMX and its products/intermediates are predicted.